Evaluation of Preeclampsia Risk in Gestational Weight Gain - Baftiu, Dardan; Abazaj, Erjona; Ali, Ela; Nikolla, Ledina (European Scientific Journal, ESJ, 2022)
Background: The incidence of obesity worldwide has increased over the last 20 years. The increase in obesity in maternal pregnancy is causing a major challenge to obstetrics practices. The aimed study was to evaluate gestational weight gain as a risk for preeclampsia in pregnant women. Methods: This cross-sectional study was conducted on 2756 pregnant women with gestational age≥37 weeks. The selection of women was categorized into two groups, 1528 normal-weight women with BMI less than 25kg/m2 and 1228 pregnant women with BMI over 25kg/m2. SPSS software version 26.0 was used to analyze data. Multivariate logistic regression described the relation of weight change to pregnancy course and outcomes. Results: A comparison between study groups appears an increase in antepartum complications in obese weight women. Besides that, arterial hypertension, pre-eclampsia, and gestational diabetes were more frequent in obese weight women compared to normal-weight women obese women. The incidence of cesarean was highest in obese women statistically significant difference from normal women with a p-value <0.005. In addition, maternal obese pregnancies were at twice the risk for delivery of infants who were macrosomia with higher odds (OR = 3.1, 95%CI = [1.09-5.8]). In perinatal outcomes, the difference in mean birth weight of the babies among normal and obese women was statistically significant (p<0.05). Conclusion: As we saw from the results of this study obesity during pregnancy was associated with pregnancy complications. To optimize all complications to maternal and fetus, weight gains during the pregnancy must be controlled and appropriate. Furthermore, studies are recommended to explore the maternal obesity complication and risk factors that influence obesity to minimize the adverse negative effect of this risk.